PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR KOMPETENSI PENGETAHUAN SISWA KELAS VA SDN 034 KIJANG REJO KECAMATAN TAPUNG KABUPATEN KAMPAR - Deni Safitri; Erlisnawati '; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is a classroom action research that aims to improve learning outcomes competences class knowledge Va SDN 034 Kijang Rejo Tapung District of Kampar through the adoption of Jigsaw Cooperative Learning Model. Based on observations in class Va SDN 034 Kijang Rejo is known that the learning competencies of knowledge on the subjects of Indonesian students on the theme of 2 Peristiwa dalam kehidupan subtema 2 Peristiwa-peristiwa penting are relatively low, with an average of 62.5. Data analysis technique used is descriptive analysis by looking at the activity of the teacher, student activity and learning outcomes of knowledge competency Indonesian theme 2 Peristiwa dalam Kehidupan of three sub-themes of Manusia dan Peristiwa Alam, theme 3 Kerukunan dalam Masyarakat subtema 1 Hidup Rukun and themes 3 Kerukunan dalam Masyarakat subtema 2 Manfaat Hidup Rukun. The average score was 62.5 basis while third cycle with an average of 77.34, bringing the total increase in learning outcomes competences Indonesian knowledge of 23.74%. Improved learning outcomes have occurred due to the increased activity of teachers and students. Results of observation of teacher activity in the first cycle of meeting 1 that is equal to 62.5%, while the third cycle of meeting 2 is 91.67%, bringing the total increase in the activity of teachers is 29.17%. The percentage of student learning activities in the first cycle of meeting 1 is 41.67%, while the third cycle was 87.5% 2 meeting, bringing the total increase amounted to 45.83% of student activity. From the results of a study it can be concluded that the adoption of Jigsaw Cooperative Learning Model can Improve Learning Outcomes Knowledge Competence Indonesian Va Grade Students of SDN 034 Kijang Rejo Tapung District of Kampar regency.Keywords: Cooperative Learning, Jigsaw, Knowledge Competence Learning Outcomes Indonesian